2019
DOI: 10.3389/fphys.2019.00325
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Ameliorates Colitis and Alters Colonic Microbiota in a Mouse Model of Dextran Sulfate Sodium-Induced Colitis

Abstract: This study evaluated the mitigating effects of dietary chlorogenic acid (CGA) on colon damage and the bacterial profile in a mouse model of dextran sulfate sodium (DSS)-induced colitis. C57BL/6J mice were randomly assigned to receive one of the following treatments: (i) basal diet; (ii) basal diet with 2% CGA; (iii) basal diet with 2.5% DSS or (iv) basal diet with 2% CGA and 2.5% DSS. Following a 2-week pre-treatment period, mice in the DSS and CGA-DSS groups received 2.5% DSS in drinking water for 5 days, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 57 publications
4
27
0
Order By: Relevance
“…Compelling evidence suggests that cytokines are crucial pathophysiological regulators of the occurrence and development of the inflammatory response of IBD ( Strober and Fuss, 2011 ). Interactions between the TNF family of receptors and their ligands are crucial in immune responses ( Zhang et al, 2019 ). The progression of inflammation is associated with TNF-α, as it is involved in the recruitment of leukocytes to the inflamed areas ( Gupta et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compelling evidence suggests that cytokines are crucial pathophysiological regulators of the occurrence and development of the inflammatory response of IBD ( Strober and Fuss, 2011 ). Interactions between the TNF family of receptors and their ligands are crucial in immune responses ( Zhang et al, 2019 ). The progression of inflammation is associated with TNF-α, as it is involved in the recruitment of leukocytes to the inflamed areas ( Gupta et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteroidetes were also reported to decrease in a commonly used model of experimental colitis induced by DSS (41). Decreased Bacteroides levels are associated with inflammatory bowel disease and ulcerative colitis (36,71) and a decreased abundance of Erysipelotrichales, Bacteroidales, and Clostridiales going along with an increase of Enterobacteriaceae, Pasteurellacaea, Veillonellaceae, and Fusobacteriaceae were observed in new-onset cases of pediatric Crohn's disease (72).…”
Section: Discussionmentioning
confidence: 97%
“…This experimental model induces colitis in mice. Of note, Bacteroidetes were reported to significantly decrease in the colon after DSS treatment (38)(39)(40)(41). Mice (C57BL/6) were treated with DSS for 4 days and samples were collected after 2 and 4 days.…”
Section: Stressful Conditions Alter the Content Of Galcer MLI In Thementioning
confidence: 99%
“…CGA has shown the capacity to alter the physical structure of intestine and the integrity of its epithelium. Zhang, Jiao, Wang, Lin, and You (2019) indicated that 2% CGA ameliorated the reduction in colon length of 2.5% DSS‐treated mouse. In porcine, 1,000 mg/kg CGA extended the length of small intestine and total intestine compared to normal basal diet (Chen et al., 2019).…”
Section: Effect Of Hca On Gut Microbiota and Functionmentioning
confidence: 99%
“…Along with the recovery from DSS‐induced colitis, Zhang et al. (2019) observed increased microbial diversity, genera Akkermansia and Lactobacillus in mice colon. No direct causal relationship has been established, but this may indicate a possible ulcerative colitis–microbiota interaction: the higher microbial diversity strengthens immunity and lowers the risk of inflammation or intestinal injury, while the suppression of proinflammatory cytokines and signaling pathways encourages the increase in Akkermansia and Lactobacillus .…”
Section: Effect Of Hca Supplementation On Gut‐related Diseasesmentioning
confidence: 99%